3D in vitro corneal models: A review of current technologies. (November 2020) - Shiju, Thomas Michael; Carlos de Oliveira, Rodrigo; Wilson, Steven E.
Abstract: Three-dimensional (3D) in vitro models are excellent tools for studying complex biological systems because of their physiological similarity to in vivo studies, cost-effectiveness and decreased reliance on animals. The influence of tissue microenvironment on the cells, cell-cell interaction and the cell-matrix interactions can be elucidated in 3D models, which are difficult to mimic in 2D cultures. In order to develop a 3D model, the required cell types are derived from the tissues or stem cells. A 3D tissue/organ model typically includes all the relevant cell types and the microenvironment corresponding to that tissue/organ. For instance, a full corneal 3D model is expected to have epithelial, stromal, endothelial and nerve cells, along with the extracellular matrix and membrane components associated with the cells. Although it is challenging to develop a corneal 3D model, several attempts have been made and various technologies established which closely mimic the in vivo environment. In this review, three major technologies are highlighted: organotypic cultures, organoids and 3D bioprinting. Also, several combinations of organotypic cultures, such as the epithelium and stroma or endothelium and neural cultures are discussed, along with the disease relevance and potential applications of these models. In the future, new biomaterials will likely promote better cell-cell and cell-matrix interactions in organotypic corneal cultures. Highlights: Three-dimensional (3D) in vitro models are excellent tools for studying complex biological systems. 3D organ models typically include relevant cell types and the microenvironment corresponding to that organ. Organotypic cultures, organoids and 3D bioprinting are three major technologies commonly used for 3D in vitro models.